2010
DOI: 10.1007/s13304-010-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic right colectomy for cancer: a single-centre preliminary experience

Abstract: The rationale for single-incision laparoscopic surgery (SILS) is minimizing morbidity, as well as improving cosmetic results of laparoscopic approach. This technique has been used for a variety of procedures and has recently been proposed for colonic resections as well. We report our preliminary experience of right colectomy, performed through a SILS approach. Five patients (3 males, 2 females, mean age 81.6 years) were selected to undergo SILS right colectomy for cancer. The procedure was carried out through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
1
20
0
2
Order By: Relevance
“…Operative times for both anterior resections and right hemicolectomies in our experience are comparable with those reported in other previously published studies [13][14][15][16]. In terms of pathological results, and especially lymph node harvest, we cannot provide definitive results given the limited number of our oncological cases.…”
Section: Right Hemicolectomysupporting
confidence: 77%
“…Operative times for both anterior resections and right hemicolectomies in our experience are comparable with those reported in other previously published studies [13][14][15][16]. In terms of pathological results, and especially lymph node harvest, we cannot provide definitive results given the limited number of our oncological cases.…”
Section: Right Hemicolectomysupporting
confidence: 77%
“…Most of the studies' conclusions were that SILS is feasible and safe for selected patients. However, it has been reported that the advantages of SILS extend beyond cosmesis to the reduction of pain [19,24], a low complication rate [18,23], early hospital discharge [19,23,24], and reduction in medical treatment costs [19,24]. A review of 149 patients demonstrated that preliminary oncologic results showed the feasibility of SILS but concluded that standardization of the technique and careful application of SILS are needed [13].…”
Section: Discussionmentioning
confidence: 99%
“…There has been no large-scale multicenter study of the use of SILS for colorectal cancer as of yet; most reports have been clinical experiences at a single institute [17][18][19][20][21][22][23][24][25][26][27]. A recent review of SILS summarized the results from 149 patients [13].…”
mentioning
confidence: 99%
“…However, time to oral intake as a measure of recovery of gastrointestinal function is prone to bias, as surgeons with an interest in laparoscopic surgery are likely to feed their patients earlier than those who perform open surgery [46]. Regarding SILC, in 39 cases of multi-institutional studies reviewed [47], average time to flatus and bowel movement was 2.2 and 2.9 days, respectively, a finding also supported by a single other report [48] (postoperative day 2-3 of first flatus). In the present study, there were only a few reports providing relevant data regarding recovery of gastrointestinal function after SIL-RH, defined as flatus passage, with only three studies comparing the median time to flatus passage between SIL-RH and ML-RH, concluding that the two surgical approaches are equivalent in terms of postoperative gastrointestinal function recovery, with no statistically significant difference between them.…”
Section: Discussionmentioning
confidence: 56%